The influence of coarse aggregate concentration on the strength of concrete and on the porosity of concrete mortar/Stambiojo užpildo koncentracijos įtaka betono stiprumui ir skiedininės dalies poringumui - Skripkiūnas, Gintautas; Vaitkevičius, Vitoldas (Journal of Civil Engineering and Management, 2001)
The results of experiments dealing with coarse aggregate concentration influence on the concrete strength and the structure of hardened cement paste and mortar of concrete are presented in the paper. Experiments were performed on concrete with dense coarse aggregate (crushed granite) which strength is more than strength of mortar and lightweight porous aggregate (expanded clay aggregate) with strength less than that of mortar. Physical and mechanical properties of concrete with dense coarse aggregate are presented in Table 1 and the concretes with the porous coarse aggregate in Table 2. The decrease of entrained air content with the increase of coarse aggregate concentration ϕσt were determined both for concretes with dense and porous coarse aggregate. The entrained air has a significant effect on concrete strength—1% of entrained air decreases the strength of concrete about 5% [11]. The influence of the coarse aggregate concentration on the compressive strength of concrete with the constant air content is presented in Figs 3 and 4. With the increase of coarse aggregate concentration the concrete strength decreases when the entrained air content in concrete is constant. The main reasons of the concrete strength reduction are the stress concentration and structural defects near the coarse aggregate. Coarse aggregate affects the structure of mortar. Dense coarse aggregate has negligible water absorption and does not change water content in mortar of concrete, and capillary porosity of mortar remains constant when the concentration of dense coarse aggregate ϕst increases (Fig 5). Porous coarse aggregate (expanded clay aggregate) has large water absorption (more than 16%), therefore water content in mortar of concrete is reduced and capillary porosity of mortar is significantly reduced when the concentration of porous coarse aggregate ϕst increases (Fig 5). The entrained air content in mortar with both dense and porous coarse aggregate decreases inverse proportionally to coarse aggregate concentration ϕst (Fig 6). The investigations have shown that suitable selection of properties and volumetric concentration of coarse aggregate can reduce stress concentration in concrete and increase the concrete strength. Article in Lithuanian. First Published Online: 30 Jul 2012